4. PGT-M FOR DE NOVO MUTATIONS – HAPLOTYPE DETERMINATION USING MORPHOLOGICALLY POOR EMBRYOS. (August 2019) - Stock-Myer, S.; Tang, P.; Twomey, A.; Kohfahl, A.; Shi, E.
Abstract : Introduction: Couples requesting PGT-M involving a de novo mutation pose a challenge when the PGT-M test used incorporates linkage analysis, as parental samples cannot be used to determine the mutant and normal allele haplotypes. In our experience, de novo mutations represent approximately 6-7% of clinical referrals, and thus it is important to have strategies in place to be able to offer PGT-M for these patients. Historically, we have employed two main strategies for these couples. If the mutation in question was paternal, we would perform single sperm analysis to determine the mutant haplotype. When the mutation was maternal, we would perform single chromosome sorting to determine the mutant haplotype. We would then confirm the phase when we obtained samples from clinical embryos. More recently, we began to question if determining phase prior to a PGT-M cycle was necessary, as we were confirming the phase as part of the cycle. We decided to evaluate if it was quicker and simpler to aim to determine phase directly from the embryos created as part of the clinical PGT-M. Materials and methods: Haplotype determination was performed for the cases, utilising biopsies from clinically usable embryos. In addition, in order to obtain enough sample numbers to determine phase, when there were less than 4-5 embryos biopsied, we also requested samples from embryos with poor morphological development. Karyomapping was the PGT-M test performed, in combination with a method to detect the mutation from MDA amplifications from the biopsied samples. A grandparental DNA reference was available in all cases to evaluate SNP coverage prior. Results: We obtained 3-7 samples from each of 14 cases to determine mutant and normal haplotypes. On 8/14 (57%) occasions, there were not enough samples from clinically usable embryos to provide us with the required sample numbers, so additional samples from embryos with poor morphological development were requested. Phase was established in all 14 cases. In all 12/14 (86%) cases the de novo mutation had a grandpaternal origin consistent with previous cases showing 89% of these de novo mutations have arisen in a sperm. Conclusions: This strategy proved successful in all 14 cases, allowing PGT-M to proceed without any delay. Additional samples from morphologically poor embryos were required 57% of the time, in order to obtain the necessary sample numbers to determine the mutant haplotype. This strategy can be employed to facilitate fast access to Karyomapping based PGT-M for cases involving de novo mutations, with a back-up strategy of using the above mentioned other methods if sample numbers are lacking.